The contribution of socio-economics to agricultural research: a review - Pachico, Douglas H. (International Center for Tropical Agriculture, 1987)
A general review is presented on how socioeconomics can contribute to agricultural research progress. Research priorities are basically determined by the identification and understanding of the farmers` problems, knowledge of their resources (type of soil, rainfall pattern), farm characteristics, and other socioeconomic aspects (labor, capital, credit, and experience). A socioeconomic analysis can contribute to assessing the impact of new technology by estimating the no. of farmers that can adapt to it, how many can really benefit from it, the amount and value of the added production, and the possible effect on prices and on nutrition for the consumer. The socioeconomic evaluation of new technology is carried out by stating the differences among agronomic treatments, and by carrying out an economic analysis through budget comparisons and the use of programming models, for which the economist should know well and clearly the farmer`s objectives and resources. Once the farmer receives and evaluates the new technology, interviews and studies allow for assessing and identifying the factors that determine its adoption. (CIAT)